2014
DOI: 10.3892/ijmm.2014.1643
|View full text |Cite
|
Sign up to set email alerts
|

7,8-Dihydroxyflavone protects human keratinocytes against oxidative stress-induced cell damage via the ERK and PI3K/Akt-mediated Nrf2/HO-1 signaling pathways

Abstract: This study investigated the effect of 7,8-dihydroxyflavone (DHF) on the expression and activity of heme oxygenase-1 (HO-1), an enzyme with potent antioxidant properties, as well as the molecular mechanisms involved. DHF markedly upregulated HO-1 mRNA and protein expression in human keratinocytes (HaCaT cells), resulting in increased HO-1 activity. DHF also increased the protein level of transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2), which regulates HO-1 expression by binding to the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
5
26
1
Order By: Relevance
“…It is well known that activation of PI3K/AKT signaling functions as a cytoprotective mechanism against oxidative stress (Mo et al 2012, Ryu et al 2014, Yang et al 2013. In this sense, our results demonstrated that, in addition to stimulating Hmox1 gene expression, treatment of Y1 cells with either ACTH or 8Br-cAMP also leads to an increase in Akt phosphorylation levels.…”
Section: Discussionsupporting
confidence: 72%
“…It is well known that activation of PI3K/AKT signaling functions as a cytoprotective mechanism against oxidative stress (Mo et al 2012, Ryu et al 2014, Yang et al 2013. In this sense, our results demonstrated that, in addition to stimulating Hmox1 gene expression, treatment of Y1 cells with either ACTH or 8Br-cAMP also leads to an increase in Akt phosphorylation levels.…”
Section: Discussionsupporting
confidence: 72%
“…Besides the oxidant stress, it was reported that Nrf2 could be activated by extracellular-regulated kinase (ERK 1/2) and protein kinase B (PKB, Akt) (Niture et al, 2014;Ryu et al, 2014). In a separate set of experiments, we further proved that SRPC could activate Akt pathways, but not Erk 1/2 pathway.…”
Section: Discussionmentioning
confidence: 58%
“…PI3K/Akt may stimulate Nrf2, a key transcriptional factor in the regulation the expression of phase-II detoxification and antioxidant response element (ARE) under oxidative stress, including HO-1. Ryu et al suggested that PI3K/Akt phosphorylate Nrf2 and facilitate its release from the Keap1-Nrf2 complex, allowing activated Nrf2 to translocate into the nucleus, then induces phase II defense enzymes, such as HO-1 [40]. Peroxynitrite, which contributes to the activation of Nrf2 and Nrf2 binding to ARE may also be involved [41].…”
Section: Discussionmentioning
confidence: 99%